1997
DOI: 10.1002/anie.199720081
|View full text |Cite
|
Sign up to set email alerts
|

Ln3Au2Al9 (Ln  Dy, Tb): Heteronuclear versus Homonuclear Bonding in Intermetallic Phases

Abstract: press. I81 Due to the strongly elongated bonds thecompounds modeled here are the first examples of cobalt(ti1) hexaamines for which an anharmonic potential is required, and for which this may be accurately parameterized. The quality of the parameters is based on structural data, including that of the yellow isomer and a set of cobalt(rn) amines with moderately long bonds, and on the computed ligand field and redox properties (see below and ref. (71). [9] a) P. Ill] CAMMAG [I21 was used for the AOM calculations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 13 publications
2
21
0
Order By: Relevance
“…This structural type includes primarily rear-earth compounds with aluminum and zinc (5,8). The structure can be also related to the BaAl -type structure as another defect version of the latter (Fig.…”
Section: K 3 Hg 11mentioning
confidence: 98%
See 1 more Smart Citation
“…This structural type includes primarily rear-earth compounds with aluminum and zinc (5,8). The structure can be also related to the BaAl -type structure as another defect version of the latter (Fig.…”
Section: K 3 Hg 11mentioning
confidence: 98%
“…Several factors, among which the size of the cation and the number of available electrons, are thought to in#uence the relative stability of the two structures, and therefore they de"ne which one is preferred (8). The compound K Hg provides not only the "rst example of an amalgam with the -La Al structure but also the "rst one with alkali metal instead of rear-earth element.…”
Section: K 3 Hg 11mentioning
confidence: 99%
“…Besides the two cited Tb 3 (Zn,Al) 11 compounds, we refer to Dy 3 Au 2.1 Al 8.9 [18] and other phases in the systems ReZneAl (R ¼ Y, Gd, Dy, Ho) [3], ReCueAl (R ¼ Y [19], Gd [20], Tb [21], Dy [22], Ho [22]) and ReAgeAl (R ¼ Y [23], Gd [24], Tb [25], Dy [22], Ho [22]). Here called X1 and X4 sites show a sharply prevailing or a total occupation by the aluminium atoms; X2 is mainly filled by Zn in the Zn-containing phases and by a mixture in the others; X3, generally with mixed occupation, is sometimes practically filled by aluminium only.…”
Section: The La 3 Al 11 -Type Phasesmentioning
confidence: 99%
“…Rare earth -transition metal -aluminium systems have been intensively investigated in recent years [1] with respect to their phase relations, crystal structures and widely varying magnetic and transport properties. Among them, the R-Au-Al systems have been poorly studied; only the existence of a certain number of isostructural ternary compounds has been reported [2][3][4][5][6][7][8][9]. Investigations of ternary Gd 2 Au x Al 1-x phases with the Co 2 Si structure type (space group Pnma) were performed in [2].…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [4][5] reported the existence of RAu 2-x Al 2+x phases (x ~ 0-1) (R = La-Yb) with the tetragonal BaAl 4 (space group I4/mmm), CaBe 2 Ge 2 (space group P4/nmm) and BaNiSn 3 (space group I4mm) structure types. Examples of novel R 3 Au 2 Al 9 compounds (R = Tb and Dy) with the orthorhombic La 3 Al 11 structure type (space group Immm) can be found in [8]. New representatives of the ScRh 3 Si 7 structure type (space group R-3c) in R-Au-Al (R = Ce-Nd, Sm, Gd-Lu) systems were discovered in [9].…”
Section: Introductionmentioning
confidence: 99%